Musical experience modulates categorical perception of lexical tones in native Chinese speakers - Wu, Han; Ma, Xiaohui; Zhang, Linjun; Liu, Youyi; Zhang, Yang; Shu, Hua (Frontiers in Psychology, 2015)
Although musical training has been shown to facilitate both native and nonnative phonetic perception, it remains unclear whether and how musical experience affects native speakers’ categorical perception (CP) of speech at the suprasegmental level. Using both identification and discrimination tasks, this study compared Chinese-speaking musicians and non-musicians in their categorical perception of a lexical tone continuum (from the high level tone, Tone1 to the high falling tone, Tone4). While the identification functions showed similar steepness and boundary location between the two subject groups, the discrimination results revealed superior performance in the musicians for discriminating within-category stimuli pairs but not for between-category stimuli. These findings suggest that musical training can enhance sensitivity to subtle pitch differences between within-category sounds in the presence of robust mental representations in service of categorical perception of lexical tonal contrasts.